Effect of weed control and nitrogen on yield, nutrient removal and quality parameters of cumin (Cuminum cyminum L.) - Yadav, S S Yadav, O P Sharma, P D Kumawat, R D (Journal of Spices and Aromatic Crops, 2004)
A field experiment was conducted at Jobner (Rajasthan), to evaluate the effect of different weed control measures and levels of nitrogen on yield, nutrient uptake and quality parameters of cumin (Cuminum cyminum). The results showed that two hand weedings at 25 and 50 days after sowing was the most effective treatment that increased the seed yield by 292.9% over weedy check. Among the herbicides, pre-plant trifluralin @ 1.08 kg ha-1 was the best treatment (4.94 q ha-1) that was comparable to trifluralin @ 2.16 kg ha-1 and pendimethalin @ 1.00 kg ha-1. Nitrogen content in seed and straw of cumin and uptake of nitrogen and phosphorus also significantly improved by different weed control treatments. Maximum protein content (17.60%) was recorded with trifluralin @ 1.08 kg ha-1 and essential oil content (2.52%) with pendimethalin @ 1.00 kg ha-1. The study also revealed that application of nitrogen @ 30 kg ha-1 which was on par with 45 kg ha-1 significantly increased seed and straw yield, nutrient uptake and protein content in cumin in comparison to application of nitrogen @ 15 kg ha-1.